2017
DOI: 10.3389/fphys.2017.00914
|View full text |Cite
|
Sign up to set email alerts
|

Non-motorized Treadmill Running Is Associated with Higher Cardiometabolic Demands Compared with Overground and Motorized Treadmill Running

Abstract: The aim of this study was to compare the cardiometabolic demands of running on a curved non-motorized treadmill (cNMT) with overground (OVR) and motorized treadmill (MOT) running. Fourteen trained male (n = 7) and female (n = 7) runners (trueV·O2peak 56.6 ± 4.0 mL.kg−1.min−1) participated in the study. Each experimental session consisted of 5 × 6-min bouts of running at progressively higher speeds, separated by 6-min rest (females 9–15 km.h−1; males 10.5–16.5 km.h−1). Oxygen consumption (trueV·O2) and heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 44 publications
1
32
0
1
Order By: Relevance
“…Thirty-four studies were included in this review and are summarised in Table 2. Non-motorised treadmill running was considered in only three of the 34 included studies [5,14,29]. This small number of studies was considered insufficient for undertaking a systematic review.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-four studies were included in this review and are summarised in Table 2. Non-motorised treadmill running was considered in only three of the 34 included studies [5,14,29]. This small number of studies was considered insufficient for undertaking a systematic review.…”
Section: Search Resultsmentioning
confidence: 99%
“…org/) and following the checklist for the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) 2015. The original protocol was prospectively registered with the International Prospective Register of Systematic Reviews (PROSPERO) in October 2017 and involved a speed are required [4], and anecdotal reports suggest they are becoming a popular training device for runners [5]. The main advantage of treadmills, compared with overground running, is that they allow various physiological measures to be captured within a limited and controlled space, greater control over performance variables such as running velocity and surface gradient, and greater control over environmental variables such as ambient temperature, wind speed and relative humidity when compared with outdoor running [6].…”
Section: Registration Of Systematic Review Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we and others showed that a curved non-motorized treadmill (cNMT; Woodway Inc., Waukesha, United States of America) can be a useful tool to study self-paced running in a lab setting. 14,15 Running on the cNMT is participant driven and provides a closer experience to overground locomotion by allowing for rapid changes of velocity, step-to-step gait variability and, most importantly, an unconsciousness decision making process to change pace. 16 The aim of this study was to compare the effect of different recovery durations on the acute physiological and perceptual responses, and the accompanying running velocities in a HIIT session performed under isoeffort conditions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, several studies found the opposite results. Some studies 8,9 found that there was no significant difference in oxygen uptake between the two modes, while others 10,11 found that the oxygen uptake of motorized-treadmill running was higher than that of overground running at the same speed. Concerning the differences in subjects, test conditions, and methods, there is no consensus in previous researches on whether the energy demands of treadmill…”
mentioning
confidence: 99%